INFLUENCE OF RISK ASSETS IMPAIRMENT ON PERFORMANCE OF NIGERIAN LISTED DEPOSIT MONEY BANKS - Adebisi, Adewale Joel; Alabi, Adeyemi Wasiu; Fatimehin, Kolawole (International Journal of Accounting & Finance Review, 2020)
Profitability is critical to the survival of Nigerian deposit money banks which is consistently been eroded by the impaired risk assets. Hence, this study was conducted to examine influence of risk assets impairment on performance of Nigerian deposit money banks. The specific objectives of the study were to; (i) determine the effect of impairment loss on operating profit; (ii) analyze effect non-performing loans ratio affect return on assets of Nigerian deposit money banks. Secondary data were collected and analysed using fixed and random effect regression analysis methods from a sample of 14 listed Nigerian deposit money banks. The study revealed that impairment loss, have significant negative relationship with operating profit (β=2.294, p‹ 0.01) and non-performing loan ratio have significant positive relationship with return on assets (β=0.067, p‹ 0.1). However, other variables such as inflation, liquidity and gross domestic product per capital also have effect on banks performance. The study concluded that risk assets impairment has significant negative influence on performance and that inflation, liquidity and gross domestic product have negative impact on profitability, while bank size has positive impact on profitability. The study recommended that; bank directors should put effective risk assets impairment test in place to boost reported profitability; the bank management should ensure effective management of liquidity ratio to boost return on equity; government policymakers should ensure that banks are mandated to disclose their risk assets impairment and expand their size by extending banking services to the unbanked areas.